The U.S. Army in Asia, 2030-2040 - Kelly, Terrence K. (RAND, 2014)
For the next 20 or more years, the U.S. relationship with China will be the fulcrum on which the East Asian security order balances. As a result, U.S. policy will need to prevent the emergence of an overtly hostile U.S.-China relationship while hedging against the possibility that one could nonetheless emerge. Such a strategy must balance between protecting U.S. interests in East Asia, where clashes with China's preferences are most likely, and cooperating with Beijing globally where the two sides have common objectives. Crafting and sustaining such a strategy will be a major challenge. It must have clear and realistic goals flowing from larger U.S. interests and strategy in the region, take into account the need for U.S.-China cooperation on a host of global security and economic matters, be flexible and responsive to Chinese moves, seek to channel Chinese conduct in favorable directions, and reflect the new realities of Asia resulting from China's increased military and economic power. The U.S. Army will have an important role to play in supporting U.S. strategy in the Asia-Pacific, primarily by providing training and support to allies and partners; helping to defend key facilities from enemy ground, air, and missile attack; providing key enabling support to the joint force; projecting expeditionary combat forces into the theater; contributing to new conventional deterrent options; and helping to encourage China's participation in cooperative military-to-military engagements.